Too old to be included: age diversity statements foster diversity yet fall short on inclusion - De Saint Priest, Oriana; Krings, Franciska; Toma, Claudia (Frontiers in Psychology, 2024)
Older employees often face discrimination and exclusion from work teams. In two scenario studies, we tested the impact of age diversity statements on the representation and inclusion of older employees in teams. In Study 1 (N = 304), participants had to create a team and were either exposed to a diversity statement or not before selecting two teammates from a list of four differing in age and gender. Then, we measured participants’ inclusive behavioral intentions towards a new, older member joining this team. Age diversity statements increased the representation but not the inclusion of older individuals in teams. In Study 2 (N = 518), we further manipulated the content of the statement (diversity or diversity and inclusion) and the organizational motive (reputation or change). We replicated the effects of diversity statements on representation. Moreover, statements also increased certain inclusive behaviors, but only when they targeted diversity and inclusion and reflected an organizational commitment to change. Taken together, these results suggest that age diversity statements foster diversity, yet fail to systematically increase inclusion.